Analysis of Factors Affecting Adoption Fintech Sharia: Literacy Perspective, Interests, Risk Management, and Sharia Compliance (Case Study on High School, Vocational School and Cileungsi Students) - Hayati, Atiek; Aditya, Mochammad Yana (Journal of Ecohumanism, 2024)
This study aims to analyze the influence of literacy, interest, risk management, and Sharia compliance on the adoption of Sharia fintech, with a case study of high school, vocational school, and university students in East Bogor. The research sample consists of 100 respondents, and the data analysis technique used is Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results show that literacy has a significant influence on the adoption of Sharia fintech, with a P- value of 0.007 (less than 0.05) and a T-statistics of 2.693. This indicates that a good understanding of Sharia fintech increases the likelihood of adoption. Additionally, interest was found to have a highly significant influence on the adoption of Sharia fintech, with a P-value of 0.000 and a T-statistics of 3.594. This confirms that individuals' desire and interest in Sharia fintech services play a crucial role in driving adoption. Risk management also proved to have a statistically significant relationship with the adoption of Sharia fintech, with a P-value of 0.011 and a T- statistics of 2.557. This suggests that the ability to manage and understand the risks associated with Sharia fintech affects the decision to adopt such services. However, the study results indicate that Sharia compliance does not have a statistically significant relationship with the adoption of Sharia fintech, with a P-value of 0.221 (greater than 0.05) and a T-statistics of 1.227. This means that in this study, adherence to Sharia principles does not significantly influence the decision of individuals or institutions to adopt Sharia fintech.